Epithelioid Angiosarcoma of the Rectum, Report of a Case - Touhara, Kazuhide; Akizuki, Shinichiro; Miyawaki, Michiyo; Sato, Daisuke; Uchida, Yuzo; Ikeda, Osamu (Nippon Shokaki Geka Gakkai zasshi, 2005)
A 55-year-old man hospitalized for hematochezia had an irregular, flat elevation palpated 2 cm orally from the anal verge. Colonoscopic endoscopy showed a type 1 tumor that bled easily. The tumor surface was dark purple and presented erosion. Histological diagnosis of biopsy specimens was poorly differenciated adenocarcinoma, and abdominoperineal excision of the rectum was done. Histological examination of resected specimens showed the rectal tumor to be epithelioid angiosarcoma. Primary epithelioid angiosarcoma of the rectum is very rare, with only 5 cases reported to the best of our knowledge.